1992
DOI: 10.1227/00006123-199212000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Cortical Morphology in Infantile Hydrocephalic Animals after Ventriculoperitoneal Shunt Placement

Abstract: As a sequel to our previous descriptions of the pathological changes induced by hydrocephalus in the infantile cerebral cortex, the study presented here has evaluated the effects of surgical decompression on cortical cytology and cytoarchitecture. Hydrocephalus was induced in 14 kittens by the intracisternal injection of kaolin at 4 to 11 days of age. Nine of these hydrocephalic animals received low-pressure ventriculoperitoneal shunts at 9 to 15 days after kaolin injection; these animals were monitored preope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
33
1
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 47 publications
4
33
1
2
Order By: Relevance
“…They reported that the diagnosis was made by ventriculography, but did not mention what occurred in the brain after surgery. Other reports have indicated that reconstitution of the cerebrum after shunting occurs only in the white matter [5,7,14,21,26,27]. In our case, the ventricles did not differ significantly in size at the first and forth MRI scans, but the syrinx was no longer recognizable at the fourth MRI.…”
contrasting
confidence: 48%
See 1 more Smart Citation
“…They reported that the diagnosis was made by ventriculography, but did not mention what occurred in the brain after surgery. Other reports have indicated that reconstitution of the cerebrum after shunting occurs only in the white matter [5,7,14,21,26,27]. In our case, the ventricles did not differ significantly in size at the first and forth MRI scans, but the syrinx was no longer recognizable at the fourth MRI.…”
contrasting
confidence: 48%
“…Both hydranencephaly and hydrocephalus have been known to occur concurrently with parvovirus infection [13,15]. On the other hand, experimentally induced hydrocephalus becomes apparent within 1 to 2 weeks of a kaolin injection [5,7,9,10,14,21,26,27] and the central canal dilates within 2 to 6 weeks [9,10]. As regards parvovirus infection, serum IgM and IgG levels have indicated that the infection is established within 3 days to 3 weeks after contact (Unpublished information; Nikken Bio Medical Laboratory Inc., Japan).…”
mentioning
confidence: 99%
“…Early-onset hydrocephalus often result in permanent deficits in motor and/or mental function with the delay of adequate treatment [1, 2]. There have been many reports of animal models in which the pathological changes of brain were investigated to determine the mechanism of neuronal damages in hydrocephalus.…”
Section: Introductionmentioning
confidence: 99%
“…There have also been many studies about recovery in the physiological metabolism and morphological structure of neonatal hydrocephalus with shunt placement [2, 8, 9, 11, 12, 13]. The condition of the neonatal brain is very different from that of the adult brain in neuronal development, myelination and cranial vault mechanics with open sutures and fontanel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation